Gender in agricultural change: Towards more inclusive innovation in farming communities. GENNOVATE report to the CGIAR Research Programs on Roots, Tubers and Bananas and Humidtropics. - GENNOVATE (2017)
This report forms part of a set of GENNOVATE research reports which pull together CRP-specific findings about how gender norms influence local level development dynamics, including the ability of individual men, women and young people to learn about and engage in innovation processes in agriculture and natural resource management. The findings presented in this report are primarily targeted to CRP research managers, scientists and research teams, and are meant to inform theories of change and intervention strategies, and to help identify opportunities for enhancing impact of agricultural research and development through the integration of gender transformative approaches.